La rendición de cuentas del ordenador primario en las haciendas públicas - Granoni, Raúl A. (1955)
The use made of the public Money must be strictly checked, the public finances being by their nature a subordinate administration. For the completion of the aim set by the giving in of accounts, all accountancy and even the concept and regulations of the finances have to be revised. The giving in of accounts has to embrace not only all the aspects, financial and patrimonial, of how the money has been used, but must show also the correlation between these two aspects. The laws and practice of this country consider the investment accounts as having a financial character. The checking must not be considered separately and independently of the accounting system; the problem has to be envisaged in its totality and among the control measures have to figure those referring to the giving in of accounts. In order that parliament could exercise his right of control, the House must count with the cooperation of a technical body, completely independent of the administrative power.